Excess weight, weight gain, and prostate cancer risk and prognosis: the PROCA-life study - Støyten, Martin; Knutsen, Tore; Stikbakke, Einar; Agledahl, Ingvild; Wilsgaard, Tom; Eggen, Anne Elise; Richardsen, Elin Helmine; Giovannucci, Edward; Thune, Inger; Haugnes, Hege Sagstuen (Acta Oncologica, 2024)
Background: Studies of excess weight and weight changes throughout adult life for prostate cancer (PCa) risk and prognosis have shown inconsistent results. Methods: In a population-based cohort, the Prostate Cancer Study throughout life (PROCA-life), 16,960 healthy men from the prospective cohort Tromsø Study (1994–2016) were included. Body mass index (BMI) and weight were measured at all four attendings, and weight change was calculated as the difference between the first and last of either Tromsø4, Tromsø5 or Tromsø6. Overall, 904 men developed PCa during 16 years of follow-up, and Poisson regression with fractional polynomials was used to investigate trends in incidence. Cox proportional hazard and logistic regression models were used to study associations between measurements of BMI and weight change and PCa risk, severity, and mortality. Results: At study entry, 46% of the participants (median age 44 years) were overweight, and 14% were obese (BMI > 30 kg/m2). We observed a 127% increase in overall age adjusted PCa incidence in the cohort during 1995 through 2019. No overall associations between BMI or weight change and PCa risk were observed. However, in sub-group analysis, weight gain among obese men was associated with a three-fold higher PCa risk (HR 3.03, 95% CI 1.39–6.58) compared with obese men with stable weight. Overweight was associated with lower risk of metastatic cancer (OR 0.48, 95% CI 0.30–0.75) at diagnosis. Men with obesity had higher risk of PCa-specific death (HR 1.72, 95% CI 1.03–2.88), while nonsmoking obese PCa cases had two times higher PCa-specific mortality compared with normal weighted PCa cases (HR 2.10, 95% CI 1.11–3.70). Interpretation: In our cohort, weight gain among obese men was associated with higher risk of PCa, and obesity was associated with higher PCa-specific mortality, especially among nonsmokers. The relationship between weight and risk for PCa remains complicated, and future studies are needed to determine clinical implications.